(untitled) (Journal of the College of Basic Education, 2024)
This research aims to: 1-building an educational program based on the aesthetic entrance. 2-the effectiveness of an educational program based on the aesthetic entrance in developing the skills of analyzing literary texts among students of the Arabic language departments in the colleges of Education. To achieve the research objectives, the researcher followed two approaches: The researcher prepared an educational program that included educational goals, educational content in light of the topics of Islamic literature, appropriate strategies, accompanying activities, educational means, and calendar methods, so it consists of the teaching manual, the student’s book, and the researcher verified its validity after Show it to a group of experts, specialists. To verify the research procedures, the researcher used an experimental design with partial control: the design of the two groups(experimental and control) random selection, with the same pre-and post-test. The research community consisted of(2164) students, and the researcher chose the Arabic language department at the Faculty of education for the humanities(Ibn Rushd) in an intentional way; to be a field for her research, as the department includes three divisions in the second stage, and through a random draw, the researcher chose Division (A) to represent the control group that studies according to the usual teaching of(34) students, while Division (B) The experimental study of the subjects of Islamic literature according to the educational program consisted of(36) students, and the research sample consisted of(70) students. The researcher rewarded the students of the two research groups with statistical parity in the following variables: chronological age, grades of the first semester of the previous academic year for the subject of Islamic literature, academic achievement of parents, the measure of language ability, the academic motivation scale, the gender variable, and the tribal test of literary text analysis skills. As for the research tool, the researcher prepared a test to measure the skills of analyzing literary texts, which included(40) paragraphs, (30) multiple-choice paragraphs, and(10) paragraphs of the essay type, its truthfulness, stability, difficulty coefficient, discriminatory power, and the effectiveness of its alternatives were verified, and the researcher prepared a criterion to correct the test, verified its truthfulness after presentation to a group of experts and specialists. The researcher herself trained the two research groups during the duration of the experiment, which lasted a full semester, namely: the first semester of the academic year (2022- 2023), the researcher finally applied the research tool, analyzed the results using a number of statistical means using the statistical program(spss), and after analyzing the data, the researcher found a statistically significant difference between the average test scores of the pre-test and the average test scores of the students of the experimental group in testing the skills of analyzing literary texts. , And the presence of a statistically significant difference between the average scores of students of the experimental group and the average scores of students of the control group in the dimensional test of the skills of analyzing literary texts. To complement the level of statistical significance, the researcher applied the ETA Square and the mcgoogian equation to measure the size of the impact of the program, and its effectiveness, so the program was effective. In light of the research results, the researcher concluded several conclusions, including: The educational program proved its effectiveness in developing the skills of analyzing literary texts among students of the second stage, therefore, the aesthetic entrance clarified many aspects of the literary text that are characterized by ambiguity, made the lecture more active, and gave it an aspect of suspense during the analysis of literary texts, and the researcher recommended a set of recommendations, including: The researcher suggested conducting similar studies aimed at finding out the effectiveness of the aesthetic entrance in other variables such as: critical reading, and literary criticism.